Providing general anesthesia for elderly patients during planned procedures — main differences compared to younger adults - Wydeheft, Lidia; Malon, Paulina; Bych, Anna; Halik, Paulina; Jusiak , Justyna; Ratajczak, Dorota; Janiak , Michał; Kędziora-Kornatowska , Kornelia (Quality in Sport, 2025)
Introduction The aging population has increased the number of older adults undergoing elective surgery, making safe, individualized general anesthesia essential. Age-related physiological changes—such as reduced cardiac, pulmonary, hepatic, and renal reserve, multimorbidity, frailty, and altered body composition—affect drug metabolism, pharmacodynamics, and tolerance to perioperative stress, resulting in higher rates of cardiovascular, respiratory, and cognitive complications compared with younger adults. Results Older patients require careful dose adjustments due to reduced drug clearance and increased sensitivity to anesthetics. Propofol-based total intravenous anesthesia (TIVA), EEG-guided depth monitoring, and agents like etomidate or dexmedetomidine improve hemodynamic stability and reduce postoperative cognitive dysfunction (POCD) and delirium. Comprehensive preoperative evaluation—including frailty screening, cognitive and functional assessment, and medication review—helps identify high-risk patients. Postoperative vigilance is needed to manage respiratory depression, inadequate pain control, and prolonged recovery. Telemedicine has proven effective for pre-anesthetic assessment, enabling early detection of cognitive impairment and reducing time, cost, and travel burden. Discussion Personalized anesthesia considering frailty, comorbidities, and altered drug metabolism improves safety. Minimizing anesthetic duration, selecting safer agents, EEG guidance, and TIVA support better outcomes, while telemedicine enhances patient-centered care. Conclusion General anesthesia in older adults requires tailored strategies addressing age-related changes and increased perioperative vulnerability. Individualized dosing, careful agent selection, structured preoperative assessment, postoperative monitoring, and telemedicine support can enhance safety and outcomes, highlighting key differences from younger patients and emphasizing a holistic, evidence-based perioperative approach.